Re:Location : Simona Denicolai & Ivo Provoost, Fabrice Gygi, Pierre Malphettes, Monika Sosnowska. - Gateau, Laurence; Macchi de Vilhena, Catherine; Villa Arson Nice, Nice (Nice : Villa Arson Nice, 2004)
Denicolai, Simona; Provoost, Ivo; Gygi, Fabrice; Malphettes, Pierre; Sosnowska, Monika
Re:Location, Villa Arson Nice, Nice, 15/11/2003 - 11/01/2004
Engels
Frans
kunstcatalogus
Keywords: Denicolai, Simona; Gygi, Fabrice; Malphettes, Pierre; Provoost, Ivo; Sosnowska, Monika